Characteristics of women who do not consult a doctor: a population-based study - Juvenal Soares Dias-; Annie Pozeczek Koltermann; Bruna Cappellesso; Josiele Flores Lisowski; Maiton Bernardelli; Paula Brustolin Xavier; Talita Donatti; Tissiani Morimoto; Fernanda Souza de Bairros; Maria Teresa Anselmo Olinto (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the prevalence of not consulting a doctor within a year. METHODS Cross-sectional population-based study, including women aged 20-60 years, living in the urban area of São Leopoldo, state of Rio Grande do Sul, in 2015. The association between variables and outcome was assessed using prevalence ratios and 95% confidence intervals (95%CI). The adjusted analysis was performed using Poisson regression with robust variance. RESULTS Among the 1,127 women participating in the study, 954 (84.6%, 95%CI 82.5-86.7) reported having consulted a physician in the year prior to the interview, 173 (15.4%, 95%CI 13.2-17.5) did not. Women belonging to lower income classes D and E, younger, and smokers had higher prevalences of no medical visits. The participants with hypertension had a higher prevalence of consultations. CONCLUSIONS There was no expected evolution in the local health system, despite the emergence of the policies implemented in this period. It is necessary to provide care for those in less favored socioeconomic conditions and for younger women.